2021
DOI: 10.2147/ott.s311038
|View full text |Cite|
|
Sign up to set email alerts
|

HS3ST2 and Its Related Molecules as Potential Biomarkers for Predicting Lymph Node Metastasis in Patients with Colorectal Cancer

Abstract: Background Lymph node metastasis is a major cause of cancer-related death in patients with colorectal cancer (CRC), but current strategies are limited to predicting this clinical behavior. Our study aims to establish a lymph node metastasis prediction model based on miRNA and mRNA to improve the accuracy of prediction. Methods GSE56350, GSE70574, and GSE95109 were downloaded from the Gene Expression Omnibus (GEO) database and 569 colorectal cancer statistics were also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[12] Since the discovery of lin-4 and let-7, the founding members of the microRNA (miRNA) family, hundreds of miRNAs have been found in viruses, plants, and animals by molecular cloning and bioinformatics methods. [13] There are more than 1000 known human miRNAs, which control more than 50% of mammalian protein-coding genes. MiRNAs can be overexpressed or inhibited in different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Since the discovery of lin-4 and let-7, the founding members of the microRNA (miRNA) family, hundreds of miRNAs have been found in viruses, plants, and animals by molecular cloning and bioinformatics methods. [13] There are more than 1000 known human miRNAs, which control more than 50% of mammalian protein-coding genes. MiRNAs can be overexpressed or inhibited in different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA is a kind of noncoding single-stranded RNA with a length of 18~25 nucleotides. It not only plays a very important role in gene expression regulation but also plays an important role in many biological processes such as cell proliferation, differentiation, apoptosis, and hematopoiesis [ 7 ]. A large number of studies have shown that the expression level of miRNA is closely related to the occurrence and development of many kinds of tumors.…”
Section: Introductionmentioning
confidence: 99%